Statins for polycystic ovary syndrome in varying resource settings: a phenome-wide association study and evidence synthesis - Zahn, Laura A.; Budine, Taylor D.; Shirey-Rice, Jana K.; Joly, Meghan M.; Wallis, Robert S.; Bernard, Gordon R.; Holroyd, Kenneth J.; Pulley, Jill M.; Jerome, Rebecca N. (Frontiers in Pharmacology, 2025)
BackgroundThere are many diseases prevalent around the globe that lack accessible and safe treatment options. Through Vanderbilt University Medical Center’s and Repurposing Essential Medicines Internationally program (Project Remedi), we aim to identify novel therapeutic uses for medications already approved and on the World Health Organization’s (WHO) Essential Medicines List (EML). We explored additional uses for simvastatin, an oral 3-hydroxy-3-methylglutaryl-coenzyme A (HMG-CoA) reductase inhibitor that is on the EML and may have additional therapeutic use outside of hypercholesterolemia.MethodsWe conducted a phenome wide association study (PheWAS) of a 3-hydroxy-3-methylglutaryl-CoA reductase (HMGCR) gene single nucleotide polymorphism (SNP) Ile638Val in 35,000 patient samples to identify novel uses for simvastatin. We then assessed biologic rationale and existing clinical evidence base related to novel phenotypes for simvastatin use for key PheWAS results.ResultsPheWAS of HMGCR variants identified a novel signal related to ovarian disease, in addition to a validating signal related to lipid dysfunction. Review of the literature substantiated involvement of HMG-CoA reductase signaling in hormone synthesis and posited involvement of dysfunction in this pathway in the development of polycystic ovary syndrome (PCOS). Synthesis of the literature regarding use of statins supported the role of these agents in improvement of symptoms and quality of life in women affected by PCOS who are not pregnant or trying to conceive, with a safety profile similar to this agent’s use in hyperlipidemia.ConclusionGiven the evidence supporting safety and efficacy of simvastatin for PCOS management, the widespread availability on the EML and affordability worldwide, simvastatin is a promising therapeutic avenue for PCOS. A large-scale efficacy trial would be valuable in further substantiating this use. Repurposing simvastatin, a widely available medicine, can provide clinicians and patients with an additional strategy for PCOS, especially in areas where medical care is limited.